1+1>2: Fiber Synergy in Aggregation‐Induced Emission. Issue 55 (3rd August 2022) - Yu, Wanting; Yu, Xiaoxiao; Qiu, Zhenduo; Xu, Chengjian; Gao, Mengyue; Zheng, Junjie; Zhang, Junyan; Wang, Gang; Cheng, Yanhua; Zhu, Meifang
Abstract: Mesoscopic aggregate is important to transfer or even amplify the molecular information in macroscopic materials. As an important branch of aggregate science, aggregation‐induced emissive luminogens (AIEgens) often show slight or even no emission in solutions but exhibit bright emission when they aggregate, which open a new avenue for the practical applications. Due to the flexible and rotor structure of AIEgens, the aggregate structure of AIEgens is highly sensitive to the surrounding microenvironment, resulting in adjustable optical properties. Fibers integrated of a multiplicity of functional components are ideal carriers to control the aggregation processes, further assembly of fibers produces large‐scale fabrics with amplified functions and practical values. In this Concept article, we focus on the latest advances on the synergy between "AIE+Fiber" for the boosted performance that beyond AIE, and their applications are presented and abstracted out to stimulate new ideas for developing "AIE+Fiber" systems. Abstract : Fibers are ideal carriers for AIEgens towards realizing sophisticated optical functions. On the single fiber level, the integration of a multiple functional components into a fiber provides adjustable microenvironments to manipulate the aggregate state of AIEgens. On the multiple‐fiber level, the assembly of multiple fiber offers entangled network to produce large‐scale fabrics to endow AIEgens with amplified functions and practical values.